Economic burden and profile of early social security benefits for multiple sclerosis in Brazil, 2014-2023 - Zago Marcolino, Miriam Allein; Belli, Karlyse Claudino; Antonini Ribeiro, Rodrigo (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objective: To assess the economic burden of multiple sclerosis (MS) on the Brazilian social security system over a 10-year period (2014 to 2023). Methods: Early benefits (men: before 65 years; women: before 60-62 years) were analyzed and their distribution according to age, sex, and region of residence was described. The economic burden con sidered the quantity, duration (months), and costs (Brazilian Reais, BRL) associated with each type of benefit. The duration of long-term benefits (retirement and social assistance) was estimated by considering the average life expectancy in Brazil, with an adjustment for the excess mortality attributable to MS, and projected up to the end of the observation period and/or expected retirement age. Expenses were calculated by considering the du ration and the number of minimum wages granted, adjusted for inflation through Decem ber 2023. Results: From 2014 to 2023, 16,149 MS-related benefits were granted in Brazil, of which 16,024 (99.2%) were early benefits (16,018 included in the economic burden analysis), with an average annual rate of 7.6 per million inhabitants. The average age at the time of benefit concession was 38.6±9.8 years. Among beneficiaries, 68.8% were women, 42.9% were employed, 19.8% self-employed, and 90.3% lived in urban areas. The total expenditure on MS-related benefits was BRL 657,247,720 during the period, with an accumulated duration of 23,717 years (284,612 months). Conclusion: Due to its disabling characteristics, MS is associated with early retirement and leaves during the prime productive years, with a burden over BRL 657 million in ten years.